Fundamentos de biologia: para professores e alunos da rede pública de ensino - Paiva, Isabela Rogério de [UNESP]; Rodrigues, João Vicente Feres [UNESP]; Toro, Luan Felipe [UNESP]; Piedade, André Luiz Mattos [UNESP]; Santos, Arnaldo Cesar dos [UNESP]; Junqueira, José Ari Gualberto [UNESP]; Okamoto, Ana Cláudia [UNESP]; Okamoto, Roberta [UNESP]; Matsumoto, Mariza Akemi [UNESP]; Rizzolo, Roelf Justino Cruz [UNESP]; Gonçalves, Alaíde [UNESP]; Casatti, Cláudio Aparecido [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
The role of the Universities in middle and high school, working both with teachers and with students, is to promote significant improvement in education. The objectives of this project are: CONTINUING EDUCATION SEGMENT FOR BIOLOGY’S TEACHER - aiming the enhancement and update of Science and Biology’s teachers from public state schools and the PRACTICING SCIENCE IN SCHOOLS SEGMENT – aiming to increase the interest of the middle and high school student for Science and Biology disciplines. For the first purpose, bimonthly meetings are scheduled at Campus of Araçatuba, where themes about life sciences and health are exposed by means of lectures and laboratory practices, administered and monitored, respectively, by UNESP professors and academics. For the second purpose, we perform weekly visits to public state schools where classes are taught to small groups of students about the great themes of life sciences and health. This work has been developed since 2010 and wide attendance, active participation and high level of interest of both teachers and students from public schools are observed. The connection between theory and practice enables the capacity of the teacher´s school to such approach, arising great interest and enthusiasm in students, which have collaborated with the teaching-learning process.

A atuação das universidades no ensino fundamental e médio, trabalhando tanto com professores quanto com alunos, é capaz de promover significativa melhoria na educação. Os objetivos deste trabalho são: SEGMENTO EDUCAÇÃO CONTINUADA PARA PROFESSORES DE BIOLOGIA – visa o aprimoramento e atualização de professores de Biologia da rede pública estadual de ensino e, SEGMENTO PRATICANDO CIÊNCIA NAS ESCOLAS – visa despertar o interesse e a valorização da disciplina de Biologia nos alunos da rede pública estadual de ensino. Para o primeiro propósito realizamos encontros bimestrais no Campus de Araçatuba, onde estão sendo abordados temas das ciências biológicas e da saúde, através de aulas teóricas e práticas laboratoriais, as quais estão sendo ministradas e monitoradas, respectivamente, pelos docentes e acadêmicos da UNESP. Para o segundo propósito realizamos visitas semanais às escolas da rede estadual de ensino onde são ministradas aulas práticas para pequenos grupos de alunos acerca dos grandes temas das ciências biológicas e da saúde. Os trabalhos estão em andamento desde 2010 e verificamos uma grande assiduidade, efetiva participação e elevado grau de interesse tanto dos professores como dos alunos da rede pública de ensino. A aliança entre as aulas teóricas e práticas esta sendo capaz de habilitar o professor com tal abordagem, a qual desperta grande interesse e entusiasmo nos alunos, o que tem colaborado com o processo de ensino-aprendizagem.
Keywords: Education; Teachers; Students; Biologic sciences; School; Educação; Professores; Alunos; Ciências biológicas; Escolas